Analisis Komparatif Profitabilitas PT Bank Panin Syariah Sekuritas Sebelum dan Sesudah Go Public - Ahmad Ramadhan; Windari Windari (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Before going public, PT Bank Panin Syariah Sekuritas had an increase in profits; however, after going public, the company's situation declined. To boost the company's profitability, PT. Bank Panin Syariah Sekuritas must be able to make the most of the money raised during the IPO process. The purpose of this study is to compare the profitability of PT. Bank Panin Syariah Sekuritas prior to and following its IPO. The approach employed in relation to the ideas advanced relates to profitability ratios, including Return On Assets (ROA), which is used as a gauge of a company's capacity to conduct business activities. If the proceeds from the company's IPO are invested in its ongoing business operations, then Keywords: Profitability Ratios, Performance, go public